DIALOG LINTAS IMAN DALAM KOMUNITAS LINTAS BUDAYA (Telaah Diskursif Polemik Ahmadiah dalam Milis Mahasiswa Pascasarjana Universitas Gajah Mada Yogyakarta) - Nur Said (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
The development of social media has made the world like folded. The actual issues to be so fast and easy to synthetically discussed through a mailing list included in the polemic issue of Ahmadiyah. This paper discussed the genealogy and characteristics of CRCS UGM student mailing list in response to issues of Ahmadiyah in Indonesia and how far it reinforce the idea of archeology students in nurturing empathetic intelligence in internal conflicts of Islam. This study was a library research that relied on documents as objects of study then to do in contents analyzed. The conclusion is in polemics on Ahmadiyah in mailing CRCS indicate an attempt to find